التدابير التنفيذية التي يحق للدولة الساحلية اتخاذها في مياهها الداخلية في مواجهة السفن الأجنبية (Latakia University Journal - Economic and Legal Sciences Series, 2015)
إذا كان التقنين من شأنه توحيد القواعد المطبقة وذلك بإخضاع أنشطة أشخاص القانون الدولي لقواعد قانونية محددة عند ممارستها لنشاطها والتقليل من المشاكل الناجمة عن الاستخدامات المتضاربة للبحار، غير أن فعالية النظام القانوني (دولي، داخلي) تتحدد من خلال ممارسة الحقوق وتحمل الالتزامات بما يضمن تنفيذه بطريقة تساهم في تعزيز الروابط بين الدول لا إفسادها. وانطلاقاً من ذلك يهدف هذا البحث للتعرف على التدابير التنفيذية التي يمكن للدولة الساحلية لضمان الامتثال لقوانينها وأنظمتها المنطبقة على القواعد والمعايير الدولية في مياهها الداخلية في مواجهة السفن الأجنبية خاصة أن هذه التدابير متعددة ومتنوعة وممارستها بطريقة تعسفية أو تحكمية قد يشكل حساسية بالغة بين الدول. The purpose of codification is to unify the applied rules through controlling the activities of international law personnel by specific legal rules while performing their activities and decreasing the problems originating from the conflicted usages of seas. However, the effectiveness of legal system, whether national or international, is identified by practicing rights and obligations to ensure its fulfillment in a way which contribute in enforcing ties among countries avoiding deterioration. Therefore, this research aims to highlight the executive measures that a coastal state can apply in order to enforce the application of its legal rules which are identical with international rules and standards in its inland water against foreign ships, especially when these measures are various and multiple and their application in a despotic and tyrannical way that may lead to severe resentment among countries.